Principles, criteria and indicators: applying Ockham’s Razor to the people-forestry link - Colfer, C.J.P.; Prabhu, Ravi; Wollenberg, Eva Karoline (1995)
This concept paper addresses those elements in the people-forest interface which we perceive as critical to sustainable forest management, based on our own training and experience, as well as two field tests of the conceptual framework (in Kalimantan and Côte d'Ivoire ). Initially, we define our use of important terms, like sustainability, well being/needs, and people; and make clear some of our assumptions. We briefly allude to four pertinent conceptual and policy issues, including the role of people in relation to the forest; the significance of maintaining cultural diversity; the relationships among cultural integrity, culture change, and stakeholder participation; and finally, policy issues pertaining to land use, population, and people's participation. The body of the paper discusses two principles, each with three associated criteria. An appendix lists principles, criteria, indicators and verifiers found useful in our field tests. We conclude briefly by describing future research plans, focused on refining our definitions of stakeholders, testing the importance of inter- generational access to resources and people's participation in sustainable forest management, and testing the applicability of such criteria and indicators for community forestry contexts.